Impacts of intensive follow-up on the long-term prognosis of percutaneous coronary intervention in acute coronary syndrome patients – a single center prospective randomized controlled study in a Chinese population. (29th August 2020) - Du, Laijing; Dong, Pingshuan; Jia, Jingjing; Li, Zhiguo; Lai, Lihong; Yang, Xuming; Wang, Shaoxin; Yang, Xishan; Li, Zhijuan; Shang, Xiyan; Fan, Ximei
Abstract: Objectives: To investigate the impact of cardiologist-coordinated intensive follow-up on the long-term prognosis of percutaneous coronary intervention in Chinese patients. Methods: We recruited 964 patients who had acute coronary syndrome and underwent successful percutaneous coronary intervention in the First Hospital Affiliated to Henan University of Science and Technology, China. Participants were randomly assigned into the intensive follow-up ( n = 479) and usual follow-up group (control group, n = 485). They received secondary prevention education during hospitalization and telephone follow-ups after discharge. The control group received telephone calls from nurses, while the intensive follow-up group received telephone calls and medical consultations from cardiologists. Both groups were followed up for 36 months. Results: (1) At 36 months, the proportions of all-cause death, cardiac death and cumulative major adverse cardiovascular events (MACEs) were 5.3%, 4.4% and 18.6% in the intensive follow-up group. These events were significantly lower than in the control group (10.1%, 9.3 % and 28.8% ( p = 0.004, p = 0.003 and p < 0.001). (2) Multivariable Cox regression analysis identified intensive follow-up as an independent predictor of survival, cardiac death-free survival and MACE-free survival. (hazard ratio (HR) = 0.487, 95% confidence interval (CI) 0.298–0.797, p = 0.004; HR = 0.466, 95% CI 0.274–0.793, p = 0.005; HR = 0.614, 95% CI 0.464–0.811, p = 0.001). Kaplan–Meier analysis revealed that patients in the intensive follow-up groups had longer survival (log rank = 8.565, p = 0.003), cardiac death-free survival (log rank = 8.769, p = 0.003) and MACE-free survival (log rank = 15.928, p < 0.001). (3) The average medical cost was significantly less in the intensive follow-up group, especially the cost for re-hospitalization (US582.74 ± 1753.20 vs . US999.32 ± 2434.57, p = 0.003). The bleeding events were similar. (4) Patients in the intensive follow-up group had significantly better controls of cardiovascular risk factors and medication adherence. Conclusions: A cardiologist-coordinated intensive follow-up program markedly decreased cardiovascular risk factors, reduced medical costs, promoted medication adherence and improved the long-term prognosis of patients after percutaneous coronary intervention in the Chinese population.